MANAGEMENT OF PRODUCTIVE WAQF FOR EMPOWERMENT OF THE UMMAH - M Muthoifin; Inayah Firdaus (Universitas Muhammadiyah Surakarta, 2020)
Research under the title of productive Waqf management strategy in order to empower students in the boarding school of Al-Fath Sukoharjo to be more aware of how productive waqf is being used for the empowerment of students, so that the management can be known. This type of research is included in qualitative research that comes from interviews and data observation. The source of this research data consist of primary data sources, researchers directly conduct interviews to the parties concerned in the management of productive Waqf in the boarding school Tahfidzul Qur’an Al-Fath Sukoharjo, researchers also use secondary data sources such as books, articles and other reference materials. The results explained that in the effort of students Empowerment, Pondok Pesantren Al-Fath Sukoharjo maximizes various ways for the management of productive waqf can continue to grow and its benefits can be perceived by the students.